Influência da frequência e intensidade de poda sobre a produtividade da jurema preta (Mimosa sp.). - Vasconcelos, Sérvulo Heber Lopes (1982)
The experiment was carried out at the Iracema Farm, in Quixadá, Ceará, Central "Sertão", with semi-arid climate; characterized by periodical droughts, with unquestionable aptitude for livestock husbandry, where caatinga comprises the native vegetation of adequate value as forrage producer during the rain season, besides an excellent adaptation to the regional ecology. The utilization of the caatinga is done by cattle, sheep and goat, through consumption of tender branches, leaves and fruits throughout the year. Among the various existing native species within the caating, the dark jurema (Mimosa sp.) is distinguished for its predominant characteristics in the large area of the semiarid Northeast. Plants of dark jurema were subjected to different kinds and intervals of pruning, in order to detect the influence of such treatments on its yiel and nutritive value. The main aspects under study were green matter, dry matter and crude protein production. The statistical design utilized was randomized blocks with nine treatments and four replications, in plots of 40 m2 (4.0 m x 10.0 m), with an area of 2,000 m2. The highest cutting frequency used originated higher production of green mather and dry matter. The crude protein yield was not significantly influenced (P < 0,05) by the higher pruning frequency; on the other hand, there was a positive effect (P < 0,05) of the pruning frequency on cases where leaves and branches were removed. The amount of ether extract, calcium, phosphorus and mineral residues were significantly influenced (P < 0,05) by the higher frequency of cutting.